VALUE PRIORITIES OF FIRST-YEARS STUDENTS AT ECONOMIC UNIVERSITY IN THE CONTEXT OF STUDYING THE DISCIPLINE «FOUNDATIONS OF RUSSIAN STATEHOOD» - ZALESSKY, MIKHAIL L.; VINNIK, VALERIA K. (Челябинский гуманитарий, 2025)
Possible ways of solving one of the tasks of the educational course “Fundamentals of Russian statehood” are consideredthe formation of a personal value system of students and its correlation with the system of traditional values of Russian society. The effectiveness of appealing to personal values for shaping the worldview and civic position of future specialists is substantiated. Based on the analysis of the literature, an algorithm for the formation of the personal hierarchy of values of the student is formulated. The data of the study of the value system of first-year students of the university, conducted in 2023-2024 on the basis of the Institute of Economics of Nizhny Novgorod State University, obtained as part of the teaching of the discipline “Fundamentals of Russian Statehood”, are presented. The research used the methodology and questionnaire of M. Rokich. This technique is one of the most popular tools for studying values, widely used in psychology, sociology and marketing. The basic idea is that values are the main guidelines in people’s lives and influence their behavior, decision-making and attitude towards various aspects of social reality. The purpose of the study is to evaluate the formed value system among students. To achieve this goal, the following tasks were set and solved: to determine the level of formation of their value system, as well as to identify and analyze the structure of this system. Based on the analysis of the research data, conclusions are drawn about the level of formation of the value system of the students participating in the experiment and the most effective ways to solve the problem under consideration. The results of the study show that the formation of a personal value system of university students, the establishment and understanding of the relationship between personal value preferences and traditional values of Russian society have significant educational potential.